Lasting liver injury following COVID-19 infection characterized by ultrasound shear wave elastography - Firouzeh Heidari; Theodore T. Pierce; Madeleine Sertic; Siddhi Hegde; David Hunt; Arinc Ozturk; Anthony E. Samir (WFUMB Ultrasound Open)
Objective: To assess for lasting hepatic injury using ultrasound shear wave elastography (SWE) in patients following COVID-19 infection. Methods: In this retrospective cohort study, patients with SWE exams between January 2019 and 2022 were categorized into three groups: 1) post-COVID-19 subjects with positive COVID-19 PCR assay, 2) random sample of contemporaneous unexposed patients with only negative prior COVID-19 PCR tests, and 3) random sample of pre-pandemic patients to address possible undiagnosed COVID-19 infection in the contemporaneous group. The average difference in median Young's modulus between post-COVID-19 patients and controls was calculated using a linear regression model after controlling for confounders. Results: 130 patients (mean age ± SD, 56 years ± 13; 66 women) were evaluated, including 30 patients after COVID-19 infection (mean age ± SD, 53 years ± 11; 15 women), 50 contemporaneous unexposed patients (mean age ± SD, 55 years ± 13; 27 men), and 50 pre-pandemic patients (mean age ± SD, 58 years ± 13; 28 women). SWE scans were performed on General Electric LOGIQ E9 or E10 an average of 44 (range, 12–81) weeks after COVID-19 infection. COVID-19 infection was associated with an average increase in median Young's modulus of 1.5 kPa (95 % CI [0.44, 2.355], p = 0.006) after controlling for age, sex, obesity, history of chronic liver disease, and time period. Post-COVID-19 patients had higher liver stiffness compared to contemporaneous controls (median = 7.58 vs 5.99 kPa, p = 0.001) but not pre-pandemic controls (median = 7.00 kPa, p = 0.51). Conclusions: COVID-19 infection is associated with increased liver stiffness, which may reflect lasting hepatic injury such as ongoing inflammation or the development of fibrosis. US SWE may serve as a noninvasive tool for long-term liver health monitoring after COVID-19 infection.